Epileptogenic Activity Induced by Teicoplanin and Effects of Some Antiepileptics in Mice - Kenshi Takechi; Takashi Ishikawa; Chiaki Kamei (Elsevier, 2008)
The present study was undertaken to clarify the epileptogenic activity induced by intracerebroventricular injection (i.c.v.) of methicillin-resistant Staphylococcus aureus (MRSA) antibiotics in mice. Teicoplanin (200 μg, i.c.v.) caused dose-related behavioral seizures such as head twitch and forelimb clonus. At the same time, the drug caused electroencephalographic (EEG) seizures characterized by spike-and-wave complex and a continuous spike with high amplitude. At a high dose (500 μg, i.c.v.), the drug caused a severe clonic convulsion followed by continuous spike and spike-and-wave complex on EEG. On the other hand, vancomycin caused no or almost no epileptogenic activity in both behavior and on EEG. Diazepam and sodium valproate dose-dependently antagonized epileptic seizures in behavior and on EEG induced by teicoplanin (500 μg, i.c.v.). In contrast, carbamazepine and ethosuximide caused no significant changes in both behavioral and EEG seizures induced by teicoplanin. From these findings, it can be concluded that teicoplanin may cause potent epileptogenic activity different from vancomycin when used clinically at extremely high doses. In addition, it may be that teicoplanin-induced seizure is closely related with the γ-amino butyric acid (GABA)-ergic mechanism. Keywords:: teicoplanin, vancomycin, electroencephalographic, antiepileptic